2014
DOI: 10.1016/j.biortech.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mesophilic and thermophilic anaerobic digestion of sugar beet pulp: Performance, dewaterability and foam control

Abstract: Digestion of sugar beet pulp was assessed in relation to biogas and methane production, foaming potential, and digestate dewaterability. Four 4-litre working volume digesters were operated mesophilically (37 ±0.5 o C) and four thermophilically (55±0.5 o C) over three hydraulic retention times. Digesters were operated in duplicate at organic loading rates (OLR) of 4 and 5 g volatile solids l -1 day -1 without water addition. Thermophilic digestion gave higher biogas and methane productivity than mesophilic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…Theoretically, thermophilic AD (TherAD) is preferred over mesophilic AD (MesAD), as recent studies have shown that: (i) TherAD is kinetically favoured over MesAD, thus resulting in a shorter retention time and poses a higher possibility to increase the organic loading rate (El Mashad et al, 1994;Angelidaki et al, 2006;Esposito et al, 2011), (ii) TherAD has a higher rate of organic matter degradation with a higher biomethane production (Gavala et al, 2003;Labatut et al, 2014;Suhartini et al, 2014), and (iii) TherAD holds a better potential to inactivate pathogens, thus complying with the EU policy for elimination of pathogens as well as obtaining Class A biosolids according to the USEPA guidelines (Labatut et al, 2014;Suhartini et al, 2014;Wagner et al, 2008;Ziemba and Peccia, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, thermophilic AD (TherAD) is preferred over mesophilic AD (MesAD), as recent studies have shown that: (i) TherAD is kinetically favoured over MesAD, thus resulting in a shorter retention time and poses a higher possibility to increase the organic loading rate (El Mashad et al, 1994;Angelidaki et al, 2006;Esposito et al, 2011), (ii) TherAD has a higher rate of organic matter degradation with a higher biomethane production (Gavala et al, 2003;Labatut et al, 2014;Suhartini et al, 2014), and (iii) TherAD holds a better potential to inactivate pathogens, thus complying with the EU policy for elimination of pathogens as well as obtaining Class A biosolids according to the USEPA guidelines (Labatut et al, 2014;Suhartini et al, 2014;Wagner et al, 2008;Ziemba and Peccia, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Two-phase AD may offer an attractive alternative to conventional one-phase anaerobic digestion because it has several advantages over traditional single-phase systems [13,41], such as a considerably shorter detention time [8,16], higher gas conversion efficiency [6,15,21] and higher methane concentration [37,6], either under mesophilic or thermophilic conditions [20]. This process has been researched in numerous fields, including those associated with waste water [24], fruits and vegetables [31], sewage sludge [7,35].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of specific substances such as protein [14], fat, oil, and grease [11] as well as suspended particles [6] was found to contribute to foam formation during the AD. Also, the AD of some substrates such as sugar beet pulp [16,17], acidic whey in connection with chicken manure [14], and slaughterhouse waste [18] is accompanied by enhanced foam formation. Kougias et al [14] reported that onefifth of the interviewed biogas plant operators could not identify the real causes of foaming in their digester.…”
Section: Introductionmentioning
confidence: 99%